2012
DOI: 10.1109/jstqe.2012.2199283
|View full text |Cite
|
Sign up to set email alerts
|

Production of Multiple Diamond-Based Single-Photon Sources

Abstract: Fluorescent emitters in diamond are considered to be a valuable resource for fields such as quantum communication, quantum photonics, and biological imaging. In this paper, we report a wide range of narrow bandwidth (∼1.5 nm) spectral emission lines arising from different color centers at room temperature. The defects were created by chemical vapor deposition of thin diamond films grown on silica substrates seeded with nanoparticles of diamond and nickel. These fluorescent lines also possess single or few cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Figure 1 summarizes the emission properties of the various single photon emitters in diamond. [22][23][24][25] and text for details). Centers for which spin manipulation of single centers has been shown are labeled with a black arrow.…”
Section: Emerging Single Photon Emitters For Qipmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 summarizes the emission properties of the various single photon emitters in diamond. [22][23][24][25] and text for details). Centers for which spin manipulation of single centers has been shown are labeled with a black arrow.…”
Section: Emerging Single Photon Emitters For Qipmentioning
confidence: 99%
“…However, implantation efficiencies of only 10 -6 render their use in nanophotonics highly challenging. Very recently, a multitude of color centers emitting between 700 and 900 nm in a CVD diamond film grown in the presence of nickel has been reported [23] , demonstrating that nickel related complexes have promising emission properties but their fabrication and identification remains highly challenging.…”
Section: Additional Emerging Single Photon Emitters In Diamondmentioning
confidence: 99%
“…An example of such a narrow-bandwidth near-infrared-emitting centre found in a CVD nanodiamond is shown in Fig. 6.2. Very recently, Castelletto et al (2012) reported a multitude of narrow-bandwidth colour centres emitting in the near infrared (700-900 nm) in a CVD diamond fi lm grown in the presence of nickel powder during the CVD process. Thus nickel is potentially responsible for the formation of many infrared-emitting complexes; however, their exact composition and structure remain unclear, as well as how to form these complexes via ion implantation.…”
Section: Nickel-related Centresmentioning
confidence: 99%
“…During CVD, a growing diamond crystal often incorporates silicon and other impurities 17 . This has been utilized extensively to engineer SiV 12 and other single photon emitters [18][19] in both individual nanodiamonds as well as polycrystalline films [20][21] . The process is, however, stochastic and improved control is needed over emitter concentrations and distributions.…”
mentioning
confidence: 99%